Food grade extraction of Chlorella vulgaris polar lipids: A comparative lipidomic study. (1st May 2022) - Couto, Daniela; Melo, Tânia; Conde, Tiago A.; Moreira, Ana S.P.; Ferreira, Paula; Costa, Margarida; Silva, Joana; Domingues, Rosário; Domingues, Pedro
Highlights: High-value polar lipids from C. vulgaris were obtained using EtOH with UAE. UAE and DCM showed the highest lipid yields and purity and EtOH the lowest yields. The polar lipidome of DCM and UAE extracts was similar, with minor differences. EtOH had lower efficiency for extraction of anionic lipids such as PI, SQDG and PG. UAE and EtOH lipid extracts revealed antioxidant activity comparable to DCM. Abstract: Glycolipids and phospholipids are the main reservoirs of omega polyunsaturated fatty acids in microalgae. Their extraction for the food industry requires food grade solvents, however, the use of these solvents is generally associated with low extraction yields. In this study, we evaluated the lipid extraction efficiency of food-grade ethanol, ultrasound-assisted ethanol (UAE) and dichloromethane/methanol (DCM) from Chlorella vulgaris cultivated under autotrophic and heterotrophic conditions. Yields of lipids, fatty acids (FA), and complex lipid profiles were determined by gravimetry, GC–MS, and LC-MS/MS, respectively. UAE and DCM showed the highest lipid yields with similar purity. The FA profiles were identical for all extracts. The polar lipidome of the DCM and UAE extracts was comparable, while the EtOH extracts were significantly different. These results demonstrated the effectiveness of UAE extraction to obtain high yields of polar lipids and omega-3 and -6-rich extracts from C. vulgaris that can be used for food applications.